Dampak Perubahan Batas Usia Nikah Terhadap Dispensasi Nikah di Pengadilan Agama - Amina, Siti Nur (Jurnal El-Thawalib, 2022)
Marriage or what is often called marriage is a common thing done by all humans on earth. In the Qur'an it is stated that living in pairs, living in pairs is the instinct of all creatures of Allah SWT, including humans. In our country, Indonesia, there is a law regarding the age of a person who wants to get married, but the law has been revised, namely in the decision of the Constitutional Court which has amended the marriage law No. 1 of 1974 concerning marriage which states that "Marriage is only permitted if a man reaches the age of 19 (nineteen) years for the woman to reach 16 (sixteen) years" which was changed or revised to Number 16 of 2019 concerning marriage which states that "Marriage is only permitted if a man and woman reach the age of 19 years". This has changed the age of women from 16 years to 19 years. The purpose of this study was to determine the impact of changing the age limit for marriage in the Padangsidimpuan City Religious Court. Based on the theoretical study and research results that have been carried out by the author at the Padangsidimpuan City Religious Court, the following conclusions can be drawn: With the enactment of Law Number 16 of 2019 it has an impact on the Padangsidimpuan City Religious Court itself, namely the increase in public submissions. Regarding cases of marriage dispensation applications, which is seen from the data, namely in October 2019 there were only 30 cases after the enactment of Law Number 16 of 2019 which proposed 59 cases from January 2020 to January 2022. And this also resulted in several people getting married early dropouts because one of the schools no longer accepts married students.